Experiences from the front-line routine consenting of surplus surgically removed tissue: without investment by the National Health Service fully informed consent for all is not available. Issue 4 (1st September 2006) - Wheeler, Janet; Agarwal, Monica; Sugden, John; Bladon, Meriel; Quirke, Philip
Abstract : The study investigated the routine introduction of a new surgical consent form containing a tissue consent section to investigate patient attitudes to the use of surplus tissue for research (after the Alder Hey inquiry) and also the differing approaches by consent takers. All surgical consent forms received in histopathology for the same 2-month period in 2 consecutive years were analysed, recording available information about the specimen, the tissue consent section and, for the second year, the consent taker. The findings showed that <5% of patients whose views were recorded disagreed with the use of their tissue for research. They also showed that the number of completed forms sent to histopathology had increased but the pattern of completion had changed very little. A wide variation between departments and also between clinicians was apparent in the levels of completion of the tissue consent section, suggesting wide variability in the quality of the consenting process. When asked, patients rarely object (<5%) but if the highest standards of consent for surgical tissue are to be achieved and the wishes of patients to donate tissue are to be effectively recorded then new resources or approaches will be needed for this process.